Cross-chest liposuction in gynaecomastia - Biju Murali; Sundeep Vijayaraghavan; P. Kishore; Subramania Iyer; Mathew Jimmy; Mohit Sharma; George Paul; Sachin Chavare (Indian Journal of Plastic Surgery)
Background: Gynaecomastia is usually treated with liposuction or liposuction with excision of the glandular tissue. The type of surgery chosen depends on the grade of the condition. Objective: Because gynaecomastia is treated primarily as a cosmetic procedure, we aimed at reducing the invasiveness of the surgery. Materials and Methods: The technique complies with all recommended protocols for different grades of gynaecomastia. It uses liposuction, gland excision, or both, leaving only minimal post-operative scars. The use of cross-chest liposuction through incisions on the edge of the areola helps to get rid of all the fat under the areola without an additional scar as in the conventional method. Results: This is a short series of 20 patients, all with bilateral gynaecomastia (i.e., 40 breasts), belonging to Simon's Stage 1 and 2, studied over a period of 2 years. The average period of follow-up was 15 months. Post-operative complications were reported in only two cases, with none showing long-term complications or issues specifically due to the procedure. Conclusions : Cross-chest liposuction for gynaecomastia is a simple yet effective surgical tool in bilateral gynaecomastia treatment to decrease the post-operative scars. The use of techniques like incision line drain placement and post-drain removal suturing of wounds aid in decreasing the scar.